Particulate matter as a possible risk factor for eosinophilic esophagitis - Albaneze, Natasha; Cotton, Cary C.; Rappazzo, Kristen M.; Gaber, Charles E.; Hoffman, Kate; Turner, Kevin O.; Genta, Robert M.; Jensen, Elizabeth T.; Dellon, Evan S. (Frontiers in Allergy, 2025)
BackgroundAir pollution, including particulate matter smaller than 10 (PM10) and 2.5 (PM2.5) µm, increases the risk for heart and lung diseases, including asthma, but has not been extensively studied as a possible etiology in eosinophilic esophagitis (EoE). We aimed to estimate the associations between exposure to PM2.5 or PM10 and EoE.MethodsIn this case-control study, using a large national pathology database of esophageal biopsies, EoE cases were defined by having biopsies with ≥15 eosinophils per high-powered field in the absence of other histopathologic causes. Controls were all other patients with esophageal biopsies. Patient residential addresses were geocoded and exposure to PM2.5 and PM10 were estimated using National Emissions Inventory data at the county level for a 5-year period including the biopsy. We estimated the odds ratios (OR) for EoE as a function of PM2.5 or PM10 exposure in tons emitted per year air using mixed logistic regression models adjusted for individual- and census tract-level characteristics.ResultsAmong 12,062 EoE cases and 229,397 non-EoE controls, the unadjusted OR for PM2.5 was 1.12 (0.99–1.25) and the adjusted OR was 1.10 (95% CI, 0.99–1.23). The unadjusted OR for PM10 was 1.04 (1.00–1.07) and the adjusted odds ratio was 1.02 (95% CI, 0.99–1.06).DiscussionExposure to higher levels of PM25 and PM10 was modestly associated with EoE case status but the association was attenuated by adjusting for potential confounders. The findings suggest any etiologic role for these particulates in EoE would be of small magnitude.